Microtus middendorffi - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus middendorffi (Poliakov, 1881). Mem. Acad. Imp. Sci. St. Petersb., 39(2): 70. TYPE LOCALITY: U.S. S. R., R.S.F.S. R., Krasnoyarsk. Krai, Taimyr Peninsula. DISTRIBUTION: N.C. and N.E. Siberia, from the Polar Ural Mtns, to the Kolyma River, and N. of Magadan. COMMENT: Subgenus Microtus; see Matthey and Zimmerman, 1961, Rev. Suisse Zool., 68:63-72; includes hyperboreus, see Gileva, 1972, Dokl. Akad. Nauk S.S.S.R., 203:689-692, and Pokrovskii et al., 1975, [Population fluctuations of animals], Acad. Sci., Sverdlovsk, p. 39-62; see also Corbet, 1978:116; but see Gromov and Polyakov, 1977:312, and Gromov and Baranova, 1981:214; OLR also retains hyperboreus as a separate species. ISIS NUMBER: 5301410008080025001 as M. middendorffi. 5301410008080016001 as M. hyperboreus. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 494, DOI: 10.5281/zenodo.7353034